Cabaran penguatkuasaan dan pelaksanaan perintah nafkah di Mahkamah Syariah Negeri Selangor dari perspektif peguam syar’ie - Zaini Nasohah (Fakulti Undang - Undang, 2009)
Syariah Court Order concerning maintenance either in interim or permanent order, is a judgement that should be obeyed by the related parties. The judgement made should be obeyed unless it has been amended or revoked by the court. The liable party who failed to act upon the court’s order will cause failure of justice. As a result justice could not be upheld. The main focus of this article is to highlight some challenges and problems of enforcement and execution of maintenance order in the state of Selangor based on the Syar’ie Lawyer’s perspective. Questionnaire has been used to collect primary data from respondents. The study shows that there are several main problems of enforcement and execution of maintenance order that need further consideration. Most of the listed problems are related to human factors. Therefore, those factors should be considered in searching for an enduring solution